Cognitive Hyperconnected Digital Transformation : Internet of Things Intelligence Evolution. - Vermesan, Ovidiu; Bacquet, Joël. (Milton : River Publishers, 2017)
Cognitive Hyperconnected Digital Transformation provides an overview of the current Internet of Things (IoT) landscape, ranging from research, innovation and development priorities to enabling technologies in a global context.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books